A Monitoring Investigation into Rock Burst Mechanism Based on the Coupled Theory of Static and Dynamic Stresses - Cai, Wu; Bai, Xianxi; Si, Guangyao; Cao, Wenzhuo; Gong, Siyuan; Dou, Linming (Rock mechanics and rock engineering, 2020)
Coal is the major energy resource in China, but the recovery of coal is constantly under the threat of rock bursts, which has been impeding safe and highly efficient coal production for decades. A better understanding of the rock burst mechanism and its monitoring and management strategies is critical to improving coal extraction efficiency with an improved health and safety environment. In this paper, rock burst mechanism was further investigated based on the hypothesis of coupled static and dynamic stresses, in which mining-induced abutment stresses were considered as the major component of the static stresses while the dynamic stresses were categorised into two types (seismic-derived and impact-derived dynamic stresses). Subsequently, on-site monitoring strategies, including microseismic (MS) monitoring, hydraulic support pressure (HSP) monitoring and seismic velocity tomography (SVT), were implemented to understand the responses of mining-induced static and dynamic stresses. To be specific, four estimation methodologies were proposed for quantitatively assessing velocity-derived static stress, seismic-derived static stress, seismic-derived dynamic stress, and impact-derived dynamic stress. These monitoring strategies have been implemented in a Chinese coal mine to understand the mechanism of a rock burst incident.